Influence of maternal age on birth and infant outcomes at 6 months: a cohort study with quantitative bias analysis. (6th January 2023) - Gebreegziabher, Elisabeth; Bountogo, Mamadou; Sié, Ali; Zakane, Alphonse; Compaoré, Guillaume; Ouedraogo, Thierry; Lebas, Elodie; Nyatigo, Fanice; Glymour, Maria; Arnold, Benjamin F; Lietman, Thomas M; Oldenburg, Catherine E
Abstract: Background: Maternal age is increasingly recognized as a predictor of birth outcomes. Given the importance of birth and growth outcomes for children's development, wellbeing and survival, this study examined the effect of maternal age on infant birth and growth outcomes at 6 months and mortality. Additionally, we conducted quantitative bias analysis (QBA) to estimate the role of selection bias and unmeasured confounding on the effect of maternal age on infant mortality. Methods: We used data from randomized–controlled trials (RCTs) of 21 555 neonates in Burkina Faso conducted in 2019–2020. Newborns of mothers aged 13–19 years (adolescents) and 20–40 years (adults) were enrolled in the study 8–27 days after birth and followed for 6 months. Measurements of child's anthropometric measures were collected at baseline and 6 months. We used multivariable linear regression to compare child anthropometric measures at birth and 6 months, and logistic regression models to obtain the odds ratio (OR) of all-cause mortality. Using multidimensional deterministic analysis, we assessed scenarios in which the difference in selection probability of adolescent and adult mothers with infant mortality at 6 months increased from 0% to 5%, 10%, 15% and 20% if babies born to adolescent mothers more often died during the first week or were of lower weight and hence were not eligible to be included in the original RCT. Using probabilistic bias analysis, we assessed the role of unmeasured confounding by socio-economic status (SES). Results: Babies born to adolescent mothers on average had lower weight at birth, lower anthropometric measures at baseline, similar growth outcomes from enrolment to 6 months and higher odds of all-cause mortality by 6 months (adjusted OR = 2.17, 95% CI 1.35 to 3.47) compared with those born to adult mothers. In QBA, we found that differential selection of adolescent and adult mothers could bias the observed effect (OR = 2.24, 95% CI 1.41 to 3.57) towards the null [bias-corrected OR range: 2.37 (95% CI 1.49 to 3.77) to 2.84 (95% CI 1.79 to 4.52)], whereas unmeasured confounding by SES could bias the observed effect away from the null (bias-corrected OR: 2.06, 95% CI 1.31 to 2.64). Conclusions: Our findings suggest that delaying the first birth from adolescence to adulthood may improve birth outcomes and reduce mortality of neonates. Babies born to younger mothers, who are smaller at birth, may experience catch-up growth, reducing some of the anthropometric disparities by 6 months of age.